Strategic Brainstorming on AI Literacy and Postgraduate Collaboration Between FKIP UNTAN and Mempawah Educators - Ahmad Yani T; Agus Wartiningsih; Halida Halida; Mimi Haetami; Hairida Hairida; Imran Imran; Kurnia Ningsih; Venny Karolina; Ajerin Karim (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
This community service program explored collaboration potential between FKIP Tanjungpura University's Postgraduate Program and 40 teachers and principals in Mempawah Regency through strategic brainstorming. The activity employed a participatory approach involving program introduction, Focus Group Discussions, evaluation, and follow-up planning. Data were collected using open-ended questionnaire survey instruments and analyzed through thematic analysis with open coding technique. Results revealed that 75% of participants viewed AI as an educational opportunity, while 22.5% recognized both benefits and risks. Primary collaboration expectations centered on graduate education access, with emphasis on scholarship support and simplified admission processes. Participants also prioritized capacity-building workshops, institutional collaboration with MKKS and MGMP, and equity in professional development opportunities. The brainstorming yielded concrete follow-up plans including MoU drafting, teacher training programs, collaborative research initiatives, and community service activities addressing educational needs in the region.